On fashion photography / photographs and text by Peter Lindbergh. - Lindbergh, Peter (Taschen, 2020)
Peter Lindbergh's seminal compendium, now published in a special anniversary edition. Through collaborations with the most venerated names in fashion, Lindbergh created new narratives with his humanist approach. This book features more than 300 images, many previously unpublished, and an adapted interview with Lindbergh.